Perkawinan Bajapuik dan Konsekwensinya dalam Keluarga (Universitas Medan Area, 2017)
Marriage is a way for people to develop offspring, therefore every marriage must meet certain requirements both based on positive law, religion and besides that there is a customary law that is not less important in the process of each crisis rites of human life, which is different but always maintained by community, this research is a normative research which sourced from primary and secondary data that is book, law, journal, research result. The result of the study that the position of men in Minangkabau adat is low and physically he has no place in his mother's house and does not have any rights as father in the household, even the boys are not paid attention, if there is divorce of men who come out of the house, on the property of the gonogini except the property of origin and if the wife dies the husband's relatives must immediately pick up the widower to return to his family, if there is a conflict of women's families who have the right to speak, this position that raises the character of Minangkabau women is always arrogant and dominating